Coda: Pages from an R.D. Book: Time and the Anthropocene - Stephen Collis (Sillages Critiques)
This paper, composed formally as an homage to Duncan’s own use of the “daybook” model, re-reads The H.D. Book as a treatise on time, working out a poetics in response to Charles Olson’s challenge, posed in the essay “Against Wisdom as Such,” to conceive of the poetic act as a practice of “bending time.” In doing so, the paper argues that it is necessary to see Duncan’s poetics as at once temporal and spatial, shaped by simultaneity as much as collage.